Complement is Activated by Coagulation and not by Chitosan in Human Whole Blood and Plasma - Baraghis, Edward; Marchand, Catherine; Rivard, Georges-Etienne; Hoemann, Caroline D. (CMBES Proceedings, 2008)
Chitosan is a biocompatible and adhesive polysaccharide scaffold composed of glucosamine and N-acetyl glucosamine. We previously showed that liquid chitosan buffered with glycerol phosphate (chitosan-GP) can be homogenously mixed into whole blood to form an in situ-solidifying clot implant that stimulates transient neutrophil chemotaxis during marrow-based regeneration of articular cartilage. Thrombin was recently shown to activate complement, a family of plasma proteases whose activation culminates in the cleavage of a C5 precursor to produce a potent neutrophil chemotactic factor, C5a. Solid chitosan particles were previously reported to activate complement in serum and plasma through the alternative pathway. We therefore tested the hypothesis that liquid chitosan-GP activates complement in human whole blood, plasma, and serum.